Advancing vascularized composite allotransplantation: essential factors for upper extremity transplant program development - Kumnig, Martin; Kobler, Caroline; Zaccardelli, Alessandra; Brandacher, Gerald; Talbot, Simon G. (Frontiers in Transplantation, 2024)
Vascularized Composite Allotransplantation (VCA) offers a unique option to restore form and function after limb loss or facial trauma that cannot be satisfactorily accomplished through traditional prosthetics or reconstructions. Establishing a successful Upper Extremity Transplantation (UET) program requires strong leadership and a structured surgical team, and extensive interdisciplinary collaboration.We conducted a qualitative study among 12 health care professionals and patients. Informed consent was obtained per protocol, and semi-structured interviews were conducted online and recorded. Participants reported their perceptions of factors that either favored or hindered a successful outcome, including functional status before and after surgery, preparation for transplant, shared decision-making, rehabilitation, and psychosocial support.Thematic analysis revealed that it is essential to establish a team comprising various disciplines well before performing VCA procedures. Defining a common goal and choosing a defined leader is a key factor in procedural success and requires open collaboration beyond what is typical. Primary described categories are interdisciplinary collaboration and skills of the VCA team, building and leading a VCA team, pre-transplant procedures, post-transplant course, and factors to consider when establishing a program.The basic roles of team science play an outsized role in establishing a VCA program. Transplantation medicine involves various overlapping scientific and medical categories requiring health professionals to consciously work together to establish complex vertical and horizontal communication webs between teams to obtain positive outcomes. In addition to medical considerations, patient-specific factors such as transparent communication, therapy plan establishment, plan adherence, and continual follow-up are significant factors to overall success.